THE PSYCHOLOGICAL STRUGGLE IN THE SONG “GIVE US CHILDHOOD” BY REMY BANDALI - Anshar Zulhelmi; Dava Diah Pamusti (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2022)
Abstract Literature is a form of art that expresses human thoughts and feelings through the beauty of language, the originality of ideas and the depth of the message. Where literary psychology is a literary study that includes works as psychological creativity. The researchers were interested in analyzing the song